Short Term Outcome of Dorsal Onlay Buccal Mucosa Graft for the Management of Bulbar Urethral Stricture - Miah, Md Latifur Rahman; Chowdhuy, Moynul Hoque; Chowdhuy, Anup Roy; Alam, Md Shawkat; Naser, Md Fazal; Babul, Md Safiul Alam (Bangladesh Journal of Urology, 2020)
Objective: To assess the success of buccal mucosal graft (BMG) urethroplasty by the dorsal onlay technique in long anterior urethral stricture (> 2 cm long). Method: This prospective interventional study was conducted in the Department of Urology, National Institute of Kidney Diseases and Urology, Sher-e-Bangla Nagar, Dhaka from January 2016 to December 2017 over a period of two years. Thirty three patients with primary and recurrent stricture of anterior urethra involving the bulbar urethra scheduled for single buccal mucosa graft urethroplasty were included in this study. Written consent was taken from each patient. Patients with stricture at posterior urethra or at distal penile urethra or stricture length <2 cm or above 6 cm were excluded from this study. Urethral malignancy cases were also excluded. All the patients were treated with dorsal onlay BMG urethroplasty. Results: Maximum patients were more than 40 years old. Mean age was 44.42 ± 7.43 years. Maximum patients had stricture more than 3 cm long. Mean length of stricture was 3.14 ± 0.65 cm. Cause of stricture was inflammatory (42.4%), idiopathic (27.3%), traumatic (21.2%) and iatrogenic (9.1%). Regarding clinical presentation, Poor urinary stream was found in 30 (90.9%) patients, urethral discharge in 12 (36.4%) patients, LUTS in 25 (75.8) patients and acute urinary retention in 9 (27.3) patients. Baseline peak urinary flow rate was 9.59 ± 1.68 ml/s. Peak urinary flow rate after 3 months of operation was 16.50 ± 2.19 ml/s and after 6 months of operation was 18.33 ± 4.40 ml/s. Post operative voided urine volume after 3 months of operation was 253.21 ± 41.22 ml and after 6 months of operation was 301.21 ± 50.38 ml. UTI was 3 (9.09) after 3 months and 5 (15.15) after 6 months of operation. Recurrence of stricture was 3 (9.09) after 3 months and 4 (12.12) after 6 months of operation. Urethra was seen narrow in 4 (12.12%) cases after 3 months and 6 (18.18%) cases after 6 months of operation. Regarding complications, Bleeding was in 4 (12.12%) cases, dribbling of urine in 5 (15.15%) cases, wound infection in 2 (6.06%) cases and 3 (9.09%) cases. Conclusion: Dorsal onlay BMG urethroplasty seems as an effective method for the management of long anterior urethral strictures. Bangladesh Journal of Urology, Vol. 22, No. 1, January 2019 p.15-19